2013
DOI: 10.2139/ssrn.2650018
|View full text |Cite
|
Sign up to set email alerts
|

How to Achieve Growth- and Equity-Friendly Fiscal Consolidation? A Proposed Methodology for Instrument Choice with an Illustrative Application to OECD Countries

Abstract: Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 71 publications
3
27
0
Order By: Relevance
“…On the tax side, S3 reveals a negative effect on TFP when shifting consumption or other taxes towards more personal taxes. This is in line with existing literature (see among others Ferreira and Pessoa, 2007;Cournède et al, 2013). Note, however, that in S3 the effect is not statistically significant.…”
Section: Direct Effects Of Fiscal Policysupporting
confidence: 92%
See 2 more Smart Citations
“…On the tax side, S3 reveals a negative effect on TFP when shifting consumption or other taxes towards more personal taxes. This is in line with existing literature (see among others Ferreira and Pessoa, 2007;Cournède et al, 2013). Note, however, that in S3 the effect is not statistically significant.…”
Section: Direct Effects Of Fiscal Policysupporting
confidence: 92%
“…An increase in unproductive expenditures financed by consumption taxes has a significant positive effect on TFP whereas when financed by other taxes (mainly property taxes) or personal taxes, the effect on TFP turns negative. These results are in line with the findings of Cournède et al (2013) and further confirm that an appropriate classification into various categories is important when analyzing the impact of taxes.…”
Section: Direct Effects Of Fiscal Policysupporting
confidence: 89%
See 1 more Smart Citation
“…Starting from earlier work on fiscal consolidation for which a single-year data file was constructed (Cournède et al, 2013), detailed expenditure and revenue items were grouped to arrive at a comprehensive breakdown. Taking this idea to the next step, this recent database takes into account not only a breakdown of fiscal items by policy area, but also includes time variation, cycle variation and structural factors which affect the quality of public finance.…”
mentioning
confidence: 99%
“…The choice of coefficients applied to the various spending and institutional inputs is crucial in this endeavour and therefore a comparison with alternative coefficients is a step to validating the soundness of the measures. The weighting schemes by Cournède et al (2013) were compared to the effects found by Fournier and Johansson (2016) in order to test the robustness of the indicators.…”
mentioning
confidence: 99%